3D networked MXene thin films for high performance supercapacitors - Nicolosi, Valeria (My University, 2024)
Maximizing the energy and power density of supercapacitors requires thick electrodes, enabling a high areal loading. Simultaneously, a sophisticated, hierarchical pore structure for the active material is needed, granting high accessibility for electrons and ions. However, porosity and thickness need to be carefully balanced to maximize the active material density while ensuring high performance. Here, we show that by forming hier- archical electrodes from Ti3C2Tx 2D nanosheets in the form of interconnected 3D networked thin films (up to ~220 nm), we can fabricate high performance thick film electrodes of up to ~50 μm with a well-defined, hi- erarchical, porous structure. By balancing porosity and thickness, we demonstrate electrodes that combine a high areal loading of up to ~7.2 mg cm 2, high material density of ~1440 mg cm 3, and high electrochemical performance of 240 F g 1 and 140 F cm 3. Thus, we achieve electrodes with a remarkable areal capacitance of ~1.4 F cm 2, even at high rates of 200 mV s 1, outperforming other state of the art MXene based electrodes of comparable density and thickness. We anticipate that this concept, will pave the way to transfer the exceptional properties of nanomaterial thin film electrodes to the next, macroscopic level, enabling the development of advanced, high-performance electrodes for practically relevant energy storage applications and beyond.
Keywords: supercapacitors; pore structure; nanomaterials; Mxene, Aeromaterial, Energy storage, High areal loading; supercapacitors; pore structure; nanomaterials